From Vagina Monologues to "Bloody Brides" and Back Again: Vaginal Myths, Street Politics, and Migrant Textile Theatrical Labour in Chinese Feminist Performances (2000s-2020s) - Wei, Yingjun (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2025)
This PhD thesis seeks to explore the ways in which contemporary feminism in China has been enacted and embodied, examining the emergence of new feminist subjects forged by these evolving practices. Central to this inquiry is an investigation into how theatre and performance have been instrumental in shaping the trajectory of Chinese feminism since the 2000s. Contemporary Chinese feminists have astutely leveraged the aesthetic and political potential of theatre as an embodied and sensory medium for activism, encapsulated by their potent motto, 'My body is the scene.' The feminist theatrical wave surged forward with the 2003 premiere of the first Chinese adaptation of The Vagina Monologues (TVM, 1996), a radical feminist play by North American feminist playwright and activist Eve Ensler. This thesis closely examines four performances: Yin Dao Du Bai (The Vagina Monologues, 2003), Yin Dao Zhi Dao (Vagina's Way, 2013), 'Bloody Brides' (2012), and Dao Yin (Saying Vagina, 2021), each of which is intricately linked, either profoundly or tangentially, to TVM and the global V-Day campaign against violence toward women. Each performance was staged in and informed by the changing landscape of Chinese feminism: from 2003 to the early 2010s, the making of TVM was a process of feminists exploring the subject position of an autonomous citizen, but from 2015 onwards, feminist theatre making had to contend with gains being eroded by state neoliberalism, an issue reflected in the fourth and final performance, Dao Yin. Overall, the study uncovers a unique trajectory for Chinese feminism, distinct from the waves of Anglophone feminism since the late nineteenth century. Chinese feminists' self-organized advocacies, from legal rights to individual female success, have condensed into a short time span of thirty years'from the 1995 UN Beijing Conference on Women onwards, roughly paralleling the timeline of Ensler's TVM. In the Conclusion, I propose the concept of `collapsed feminisms' to encapsulate how Chinese feminist theatres from 2003 to 2021 staged an extremely complex scene where these diverse feminisms overlapped and `collapsed' together.
APPROVED
Keywords: Vaginal Iconography; Street Performance; Performative Activism; Theatrical Labour; Feminist Theatre